Heterotopic ossification related to the radial tuberosity: a tumour mimic. Issue 1 (January 2016) - Shah, A.; James, S.L.; Botchu, R.; Davies, A.M.
Abstract : Aim: To present the imaging features of heterotopic ossification (HO) related to the radial tuberosity initially referred as a suspected sarcoma. Materials and methods: Local institutional review board approval was obtained. A retrospective search of the oncology database was conducted to identify cases of ossification related to the radial tuberosity, referred to the supra-regional orthopaedic oncology centre as a suspected sarcoma. Furthermore, cases of soft-tissue sarcoma (STS) of the proximal forearm were also identified. The imaging findings were reviewed for all relevant cases. Results: Over a 10-year period, 50 cases of STS of the forearm were identified with 23 involving the proximal forearm. STS was intimately related to the radial tuberosity in 52% (12/23) of these cases. There was no calcification or ossification related to the radial tuberosity in any of these sarcomas. During the same 10-year period, five cases of HO related to the radial tuberosity were identified. Demographics of these five cases revealed no significant sex predominance with a median age of 60 years. No obvious precipitating cause or predisposing condition was demonstrated. All five cases had radiographic evidence of ossification ranging from 20–53 mm in maximal dimension. Apart from one patient who had extensive ossification extending up the distal biceps tendon, the biceps tendon was otherwise normal on magnetic resonance imaging (MRI). There was only one case of mild osseous oedema of the proximal radius. Conclusion: No STS adjacent to the radial tuberosity was associated with ossification related to the radial tuberosity. Ossification related to the radial tuberosity is a benign entity and radiologists need to be aware of this tumour mimic. Highlights: Radial tuberosity ossification is benign. Ossification localised to the radial tuberosity represents enthesopathy. Proximal forearm soft tissue sarcomas do not present with ossification or calcification limited to the radial tuberosity.